Smartphone Use and Musculoskeletal Disorders: A Systematic Review of Epidemiological Evidence and Potential on Inflammatory Mechanisms - Nurul Afifah Hijami; Maya Ulfah (Indonesian Journal of Life Sciences, 2026)
Smartphone use among adults has increased and often involves prolonged exposure with sustained non-neutral neck posture. Epidemiological studies report a high prevalence of neck and shoulder pain among frequent users. Biomechanical loading of the cervical spine is considered a main mechanism, while inflammatory processes have been proposed as an additional pathway. This systematic review evaluated the association between smartphone use and musculoskeletal complaints, focusing on inflammatory biomarkers as a potential biological mechanism. The review followed PRISMA 2020 guidelines. Searches were conducted in PubMed and ScienceDirect for peer-reviewed studies published between 2018 and 2025. Eligible studies included adults aged 18 years or older who reported smartphone use exceeding 2 to 3 hours per day. Exposure was commonly assessed using self-report questionnaires or structured surveys. Studies examining neck or shoulder outcomes, posture, or inflammatory biomarkers were included. Observational studies, randomized controlled trials, and ergonomic interventions were eligible. Thirty studies met the inclusion criteria. Most reported significant associations between prolonged smartphone use, sustained neck flexion, and musculoskeletal pain in the neck and shoulders. Prevalence ranged from moderate to high among students and workers with a daily use of 3 to 9 hours. No included study directly measured inflammatory biomarkers in general smartphone users. Related evidence indicates elevated IL-6 and C-reactive protein in sedentary populations with high device exposure.